2023
DOI: 10.3390/ijms241914882
|View full text |Cite
|
Sign up to set email alerts
|

The IGF1 Signaling Pathway: From Basic Concepts to Therapeutic Opportunities

Haim Werner

Abstract: Insulin-like growth factor 1 (IGF1) is a peptide growth factor with important functions in multiple aspects of growth, development and metabolism. The biological actions of IGF1 are mediated by the IGF1 receptor (IGF1R), a cell-surface protein that is evolutionarily related to the insulin receptor (InsR). The effects of IGF1 are moderated by a group of binding proteins (IGFBPs) that bind and transport the ligand in the circulation and extracellular fluids. In mechanistic terms, IGF1R function is linked to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…IGF1 is well known to play a pivotal role in growth, development and metabolism [ 40 ]. Previous studies have shown that IGF1 contributes to eye growth as well as myopia development [ 41 , 42 ], and, in fact, the IGF-1 gene on chromosome 12q23.2 is located within the high-grade myopia locus, MYP3 interval, which has been mapped for autosomal dominant high myopia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 is well known to play a pivotal role in growth, development and metabolism [ 40 ]. Previous studies have shown that IGF1 contributes to eye growth as well as myopia development [ 41 , 42 ], and, in fact, the IGF-1 gene on chromosome 12q23.2 is located within the high-grade myopia locus, MYP3 interval, which has been mapped for autosomal dominant high myopia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the growth factors, the insulin-like growth factor 1 (IGF1) is well known for its involvement in tumorigenesis, metastasis and drug resistance ( 4 ). The axis represented by IGF1 and its receptor, the insulin-like growth factor 1 receptor (IGF1R), is deregulated in many cancer cell types ( 5 ). In addition to its direct involvement in cancer cell survival and proliferation, the IGF1/IGF1R axis is also appearing as a key factor involved in the regulation of immunity and may be an important player in modulating the immune-compartment of the TME, and thus, the cancer-related immune response.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Additionally, various neuropeptides have been suggested to regulate the expression and production of IGF1. [ 23 ] Studies have also demonstrated that CD11c + microglia highly expressed IGF1 to alleviate neurological pathologies. [ 24 ] Given the pivotal role of TREM2 in regulating cellular signaling pathways, such as CD11c in microglia [ 25 ] and peptide formation and kinase cascades, we hypothesize that TREM2 may activate other signaling pathways, such as CD11c‐related pathways and various kinase cascades, to induce the expression of Igf1 mRNA and subsequently enhance IGF1 production.…”
Section: Discussionmentioning
confidence: 99%